O književni osebi in horizontu pričakovanj v predoperativnem in operativnem obdobju otrokovega bralnega razvoja - Kordigel Aberšek, Metka (Jezik in slovstvo, 2003)
The paper attemts to present the results of the second part of a research study of the child's reception abilities, linked to he child's mental schema of a fairy tale, which was carried out at the Department of Primary Education at the Faculty of Education, University of Maribor. Within a quantitative analysis of the results of a productiove creative procedure and an analysis of the results of a guided interview, the horizon of the child's expectations, linked to fairy tale fictional characters, was studied. The suitability of the approximate goals regarding literary reception, understanding and evaluation of fictional characters in general (goal 4.1.1/2:1,2,3) and fairy tale fictional characters in particular (goal 4.1.1/4.2), as specified in the curricula for the first and the second three-year cycles of tje 9-year primary school was also indirectly checked.
Keywords: didactic method; didaktika; pouk književnosti; pravljica; fairy tale; branje; primary school; osnovna šola